STRATEGI INTERNALISASI AQIDAH MELALUI MANAJEMEN PENDIDIKAN BERBASIS TAUHID UNTUK ANAK USIA DINI DI CINTA MEDINA SCHOOL SURAKARTA - ‘Ain, Aufa Qutratu; Ali, Mohammad; Wachidi (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
This study investigates the strategy for aqidah (Islamic creed) internalization through tauhid-based educational management at Cinta Medina School Surakarta, an Islamic preschool institution that embeds tauhid values into its curriculum, instructional activities, and institutional culture. Using a descriptive qualitative approach, data were obtained through observation, in-depth interviews with the school’s foundation management, and document analysis. The findings indicate that aqidah internalization is systematically implemented through four core components: tauhid-focused instructional planning, integration of thematic and ritual activities such as dhuha and dzuhur prayer in congregation, collaborative engagement of teachers and parents, and reflective narrative-based spiritual assessment. A key innovation is the implementation of a dedicated subject called “First Tauhid,” delivered twice weekly using fun learning methods rooted in fitrah development. The study affirms the relevance of the Islamic Early Childhood Education framework and Al-Attas’ Theory of Fitrah, and contributes a replicable, holistic model of Islamic educational management for early childhood institutions. Keywords: Islamic education; Early childhood; Aqidah internalization; Educational management; Tauhid values